(untitled) (Nigerian Journal of Physiological Sciences, 2021)
This study tested the hypothesis that the hypotensive effect of the aqueous calyx extract of Hibiscus sabdariffa (HS) occurs through autonomic mechanisms that may be associated with a reduction in the double product (DP) of the heart. Experiments were performed in accordance with the Principles of the Declaration of Helsinki. Following ethical approval and informed consent, the Harvard step test (HST) was performed in healthy subjects (n=14) to activate the autonomic nervous system before and after the oral administration of 15mg/kg HS. The blood pressure (BP) and heart rate (HR) responses were measured and DPs and the mean arterial pressure (MAP) were calculated. Results were expressed as mean ±SEM. Paired t-test and one way ANOVA with a posthoc Bonferoni test were used for statistical analyses. P<0.05 was considered significant. HST without HS resulted in a significant rise in MAP, HR and DP (112.6±2.7mmHg, 97.7±2.5/min and 12630.0±642 mmHg.bpm) from the basal values (98.5±2.3mmHg, 76.5±2.0/min and 8730.7±354.9 mmHg.bpm, P<0.001, P<0.01 and P<0.001 respectively). In the presence of HS, HST-induced changes (∆MAP=7.8±1.6mmHg; ∆HR=8.1±1.6/min; ∆DP= 1113.6±103.4 mmHg.bpm) were significantly dampened compared to its absence (∆MAP= 13.3±2.6mmHg; ∆HR=17.0±3.7/min; ∆DP= 3899.3±287.2 mmHg.bpm; P<0.001, P<0.01 and P<0.0001 respectively). The HST-induced increase in BP, HR and DP suggest sympathetic nervous system (SNS) activation and parasympathetic nervous system (PNS) withdrawal associated with an increased cardiac O2 consumption and workload. These were dampened by HS suggesting that its hypotensive effect occurs through the inhibition of SNS activation, PNS withdrawal and an associated reduction in cardiac O2 demand and workload.